2019
DOI: 10.1186/s12872-019-1176-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac pacing challenge in Sub-Saharan Africa environnement: experience of the Cardiology Department of Teaching Hospital Aristide Le Dantec in Dakar

Abstract: Background Cardiac pacing is a growing activity in Sub-Saharan Africa. There is little data on the characteristics of this interventional treatment in our regions. The goal was to evaluate the results of cardiac pacing in a referral service in sub-Saharan Africa. Methods We carried out a twelve-year retrospective study (from January 1st, 2004 to December 31st, 2015) in the Cardiology Department of Aristide Le Dantec University Hospital. This work included all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
(20 reference statements)
0
3
1
Order By: Relevance
“…The present study has shown that, patients waited on average 38.35 days for surgery as opposed to an average of 8 days reported in Senegal 30 . The longer pre-operatively stay of the majority of patients in this study can be associated to the lack of consumables and limited number of cardiothoracic surgeons in the unit.…”
Section: Discussioncontrasting
confidence: 65%
“…The present study has shown that, patients waited on average 38.35 days for surgery as opposed to an average of 8 days reported in Senegal 30 . The longer pre-operatively stay of the majority of patients in this study can be associated to the lack of consumables and limited number of cardiothoracic surgeons in the unit.…”
Section: Discussioncontrasting
confidence: 65%
“…Pneumothorax occurred in 2.54% of study participants in our study, which is about in line with other studies’ findings. 8 , 15 , 16 , 18–22 When compared to individual studies, it is greater than those conducted in Taiwan (0.6%), the United States (1.3%), the United States (1.5%), Denmark (0.9%), the Netherlands (2.24%), Norway (2.8%), Cameroon (1.6%), and Senegal (0.6%), but lower than those made in Spain (3.9%). 8 , 15 , 16 , 18–22 This variation in pneumothorax magnitude between studies may be explained by variations in professional experience among centres, variations of venous access for implantation, and the inclusion of patients with CRT and ICD in quantifying the pneumothorax rate in some of these researches.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lead dislodgment occurred in 2.5% of patients; this rate was higher than that of the United States (2.4%), Poland (2.4%), the Netherlands (4.9%), Iraq (0.25%), and Senegal (0.6%), but lower than that of Kenya. 9 , 11 , 13 , 15 , 23 , 25 The use of various fixation types and differences in follow-up duration in the studies can account for this disparity in lead dislodgement rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations